Low‑pressure and liquid level fber‐optic sensor based on polymeric Fabry–Perot cavity (2021)
An experimental study of the interaction between a Mylar® polymer flm and a multimode fber-optic is presented for the simultaneous fber-optic detection of low-pressure and liquid levels. The junction between the polymer and optical fber produces an interference spectrum with maximal visibility and free spectral range around 9 dB and 31 nm, respectively. Water pressure, which is controlled by the liquid level, stresses the polymer. As a result, the spectrum wavelength shifts to the blue region, achieving high sensitivities around 2.49 nm/kPa and 24.5 nm/m. The polymeric membrane was analyzed using a fnite element model; according to the results, the polymer shows linear stress response. Furthermore, the membrane material is operated below the yielding point. Moreover, the fnite analysis provides information about the stress efect over the thickness and the birefringence changes. This sensor exhibits a quadratic polynomial ftting with an adjusted R-squared of 0.9539. The proposed sensing setup ofers a cost-efective alternative for liquid level and low-pressure detection